Enhancing healthcare decision-making process: Findings from orthopaedic field - Irene Schettini; Gabriele Palozzi; Antonio Chirico (Administrative Sciences, 2020)
In the healthcare field, the decision-making process is part of the broad spectrum of 'clinical reasoning', which is recognised as the whole process by which a physician decides about patients' treatments and cares. Several clinicians' intrinsic variables lead to this decisional path. Little is known about the inference of these variables in triggering biases in decisions about the post-discharge period in the surgical field. Accordingly, this research aims to understand if and how cognitive biases can affect orthopaedists in decision-making regarding the follow-up after knee and hip arthroplasty. To achieve this goal, an interview-based explorative case study was run. Three key-decisional orthopaedic surgeons were interviewed through a quality control tool aimed at monitoring the causes and effects of cognitive distortions. Coherently with the literature, eight biases come to light. All the interviewees agree on the presence of four common biases in orthopaedic surgery (Affect heuristic, Anchoring, Halo effect, Saliency). The other biases (Groupthink, Availability, Overconfidence, Confirmation), instead, depending on specific physicians' intrinsic variables; namely: (i) working experience; (ii) working context. This finding contributes to the debate about the application of cognitive tools as leverage for improving the quality of clinical decision-making process and, indirectly, enhancing better healthcare outcomes.
Keywords: 350; clinical decision-making process; clinical reasoning; cognitive biases; orthopaedics; follow-up decision; healthcare decision